Proceedings of the 21st International Conference on Computational Linguistics and the 44th Annual Meeting of the ACL - ACL '06 2006
DOI: 10.3115/1220175.1220219
|View full text |Cite
|
Sign up to set email alerts
|

Automatic classification of verbs in biomedical texts

Abstract: Lexical classes, when tailored to the application and domain in question, can provide an effective means to deal with a number of natural language processing (NLP) tasks. While manual construction of such classes is difficult, recent research shows that it is possible to automatically induce verb classes from cross-domain corpora with promising accuracy. We report a novel experiment where similar technology is applied to the important, challenging domain of biomedicine. We show that the resulting classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The three levels reflect different granularity in the semantics of the verb classes as illustrated in Figure 1. These clusters were annotated by 4 domain experts and 2 linguists, were used to create the gold standard (Korhonen Figure 1: Examples of the verb classes introduced by Korhonen et al (2006). et al, 2006).…”
Section: Verb Clustersmentioning
confidence: 99%
“…The three levels reflect different granularity in the semantics of the verb classes as illustrated in Figure 1. These clusters were annotated by 4 domain experts and 2 linguists, were used to create the gold standard (Korhonen Figure 1: Examples of the verb classes introduced by Korhonen et al (2006). et al, 2006).…”
Section: Verb Clustersmentioning
confidence: 99%
“…Next, to obtain as comprehensive subcategorization frequency information as possible, up to 10,000 sentences containing an occurrence of each of these verbs were included in the input data for subcategorization acquisition. These sentences were extracted from five different corpora, including BNC (Korhonen et al, 2006). We used these data to calculate similarity between verbs.…”
Section: Subcategorization Informationmentioning
confidence: 99%
“…As this pilot study showed that fine-grained domain-specific semantic patterns for verbs can be obtained automatically, we would like to port the approach to a domain where fine-grained typing is of paramount importance. This is the case with the biomedical domain, where for instance verbs of biological interaction, such as inhibit or activate are semantically underspecified Korhonen et al, 2006). However, the specific biological interactions come only through the details of the actual arguments participating in the interaction .…”
Section: Summary and Future Workmentioning
confidence: 99%